Evaluation of the Psychometric Properties of the Ethnocentrism Scale - Asena Albayrak; Özkan Tütüncü (Journal of Economy Culture and Society)
Ethnocentrism is the evaluation of different cultures in various societies according to the preconceptions of one’s own culture and with one’s own culture at the center. It has some distinct features compared to tourism, since one of the main motivations of tourism is to know different cultures. The purpose of this study was to adapt “the ethnocentrism scale,” which was developed by Neuliep and McCroskey, into Turkish and to test the validity and reliability analysis of the scale. The study was conducted through a self-administered questionnaire and distributed to 422 residents of Alaçatı, Izmir (Turkiye). As a result of Robust Diagonally Weighted Least Squares (RDWLS) analysis, it was concluded that the adapted ethnocentrism scale was three-dimensional rather than one-dimensional as in its original structure. None of the items were excluded from the study. Results showed that scale is valid and reliable with some limitations for the Turkish version. The ethnocentrism scale was found in the literature for the first time in three dimensions, and the names of the dimensions were determined for the first time in this study.